Effects of exercise on sleep problems in breast cancer patients receiving radiotherapy: a randomized clinical trial - Steindorf, Karen; Wiskemann, Joachim; Schmidt, Martina (Breast cancer research and treatment, 2017)
Purpose: Sleep problems frequently affect breast cancer patients during and after treatment and reduce their quality of life. Treatment strategies are mostly unknown. Thus, we assessed within a randomized controlled trial whether a 12-week exercise program starting with the radiotherapy influences sleep trajectories. Methods: Sleep quality and problems were assessed via self-report in 160 breast cancer patients before, during, and 2, 6, and 12 months after participation in a trial investigating resistance exercise versus a relaxation control group concomitant with radiotherapy. As additional comparison group, 25 age-matched healthy women exercised and followed identical study procedures. Ordinal logistic regression analyses were used. Results: The exercise intervention significantly decreased sleep problems compared to the relaxation control group (scale: 0-100, with between-group mean differences of −10.2 (p = 0.03) from baseline to the end of radiotherapy and −10.9 (p = 0.005) to the end of the intervention), with sleep problems decreasing in the exercise group and increasing in the control group. At 12 months, differences were still observed but statistically non-significant (mean difference = −5.9, p = 0.20). Further adjustment for potential confounders did not change the results. Several determinants of sleep problems at baseline were identified, e.g., previous chemotherapy and higher body mass index. Conclusions: Our randomized exercise intervention trial confirmed results from earlier but mostly smaller studies that radiotherapy aggravates sleep problems in breast cancer patients and that exercise can ameliorate these effects. Considering that sleep quality can be a major predictor of quality of life, our findings are of substantial importance to many breast cancer patients.
Gesehen am 18.09.2018